Role of Serum Procalcitonin and C-Reactive Protein in Predicting Surgical Site Infections After Head and Neck Surgeries - Nishat Afroz, Asad Ali Shah, Hameedullah Achakzai, S. M. Qaisar Sajjad, Muhammad Tahir Shah, M. Shakil Zari Khawri Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical site infections (SSIs) are a frequent postoperative complication in head and neck surgeries due to the high microbial load of the upper aerodigestive tract. Early detection is essential because clinical signs often appear late and may delay timely management. Serum biomarkers such as procalcitonin (PCT) and C-reactive protein (CRP) may help identify infections earlier than clinical assessment alone. Objective: To evaluate the diagnostic performance of serum PCT and CRP in predicting SSIs following elective head and neck surgeries. Methods: This prospective multicentre study was conducted from June 2022 to April 2023 at Nishtar Hospital Multan, Bolan Medical Complex Hospital Quetta, and Sir Syed College of Medical Sciences for Girls Karachi. A total of 120 adult patients undergoing elective head and neck procedures were enrolled. Serum PCT and CRP levels were measured preoperatively and on postoperative days 1, 3, and 5. SSIs were diagnosed based on CDC criteria. Receiver operating characteristic (ROC) analysis was performed to determine the predictive accuracy and optimal cut-off values of both biomarkers. Results: Of the 120 patients, 28 (23.3%) developed SSIs. PCT levels were significantly higher in the SSI group beginning on postoperative day 3 (0.74 ± 0.18 ng/mL vs. 0.28 ± 0.09 ng/mL; p < 0.001), with further elevation by day 5. CRP also showed significant elevation in the SSI group, particularly on postoperative day 3 (118.6 ± 26.3 mg/L vs. 63.4 ± 18.7 mg/L; p < 0.001). ROC analysis demonstrated superior diagnostic accuracy of PCT (AUC 0.89; optimal cut-off >0.52 ng/mL) compared with CRP (AUC 0.82; cut-off >82 mg/L). PCT showed higher specificity and earlier separation between infected and non-infected patients. Conclusion: Serum procalcitonin is a more accurate and earlier predictor of SSIs after head and neck surgeries compared with C-reactive protein. Combined interpretation of both markers enhances early postoperative infection surveillance and supports timely clinical decision-making. Keywords: Procalcitonin; C-reactive protein; surgical site infection; head and neck surgery; postoperative biomarkers; infection prediction; inflammation markers.